2021
DOI: 10.1002/mmce.22779
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized dual stop band frequency selective surface with broadband linear co to cross polarization conversion ability

Abstract: This work presents a miniaturized angularly stable frequency selective surface (FSS) on a single layer substrate. Unit cell comprises of convoluted circular rings connected cross dipole and linear arrow headed dipole printed on both sides of the substrate. A closely spaced dual stop band resonances are obtained at 10 and 14.3 GHz with frequency ratio of 1.43. FSS shows a À 10 dB stopband bandwidth (BW) from 7.32 to 11.05 GHz (40.61%) and 12.68 to 15.97 GHz (22.97%) with >30 dB stop band rejection at center fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Farooq et al 6 presented a very small‐sized FSS of dimension 07 λ c × 0.07 λ c to resonates at 2.5 and 5.45 GHz. Dey et al 7 reported a small FSS of a unit cell size 0.13 λ c × 0.13 λ c to cover the stopbands at 7.32–11.05 and 12.68–15.97 GHz. Li et al 8 reported multiresonating FSS of unit cell size 0.3 λ c × 0.3 λ c to offer stopbands at 2.5–5.5 and 6.2–10 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…Farooq et al 6 presented a very small‐sized FSS of dimension 07 λ c × 0.07 λ c to resonates at 2.5 and 5.45 GHz. Dey et al 7 reported a small FSS of a unit cell size 0.13 λ c × 0.13 λ c to cover the stopbands at 7.32–11.05 and 12.68–15.97 GHz. Li et al 8 reported multiresonating FSS of unit cell size 0.3 λ c × 0.3 λ c to offer stopbands at 2.5–5.5 and 6.2–10 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterials are artificially engineered materials that have exotic properties like negative electric permittivity and magnetic permeability. It can easily alter the polarisation states of EM waves by manipulating surface waves by portable planar structures called metasurfaces (2D equivalent of 3D MM) [12][13][14][15][16][17][18][19]. Metamaterials can be used for designing highly sensitive refractive sensors based on strong magnetic resonance [20].…”
Section: Introductionmentioning
confidence: 99%